The effects of light and a combination of growth regulators on the induction of somatic embryogenesis in orchid Rhynchostylis gigantea (LindI.) Ridl. - Sri Rianawati,; Dasumiati,; Rahmi, Nur Amelia; Kurniati, Ridho Kurniati; Mulyaningsih, Enung Sri (Penerbit Universiti Kebangsaan Malaysia, 2023)
The squirrel-tail orchid (Rhynchostylis gigantea) belongs to the Orchidaceae family. This orchid is indigenous to Southeast Asia and is scented and arranged in a bouquet of dangling stems. Its uniqueness makes it commercially desirable. In vitro culture has been utilized for orchid proliferation for a very long time to aid in the development of orchid seedlings. However, not all orchid species react the same way. Through somatic embryogenesis without gamete fusion, in vitro culture techniques can produce new plants during the entire embryonic phase. Endogenous and exogenous hormones, as well as light, influence the success of embryogenesis. Determining the optimal environmental parameters (light, combination and concentration of growth regulators, and their interaction) for inducing somatic embryogenesis from leaf explants in R. gigantea is the purpose of the present study. The leaves of R. gigantea clone 19 were utilized as explants in this investigation, utilizing a completely random factorial design. The first factor is a combination of growth regulator types and concentrations, and the second factor is light. Explants that are alive and growing at a rapid rate indicate that the in vitro culture is successful. Light and the combination of growth regulators significantly affected the percentage of viable explants, the beginning date of callus formation, and the number of embryogenic calluses produced. The interaction of two components (light and a combination of growth regulators) did not affect the three characteristics, with the exception of the proportion of somatic embryogenesis. Incubation in the dark is the optimal environment for initiating somatic embryogenesis in explants. The optimal combination of plant growth regulators for inducing somatic embryogenesis was 0.5 mgL-1 TDZ and 0.1 mgL-1 BAP. Bright light and a concentration of 1.0 mgL-1 TDZ + 0.1 mgL-1 BAP were the optimal interaction conditions for the induction of somatic embryogenesis in R. gigantea.